2011
DOI: 10.1021/ct200146j
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Constant pH Molecular Dynamics in Explicit Solvent with pH-Based Replica Exchange

Abstract: A computational tool that offers accurate pKa values and atomically detailed knowledge of protonation-coupled conformational dynamics is valuable for elucidating mechanisms of energy transduction processes in biology, such as enzyme catalysis and electron transfer as well as proton and drug transport. Toward this goal we present a new technique of embedding continuous constant pH molecular dynamics within an explicit-solvent representation. In this technique we make use of the efficiency of the generalized-Bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
561
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(581 citation statements)
references
References 56 publications
18
561
1
1
Order By: Relevance
“…We also demonstrated that the potential artifacts are negligible in the hybrid-solvent scheme where GB model is applied to propagating the titration coordinates. 15 However, a varying net charge is a major issue that needs to be addressed for developing an accurate CpHMD method based on the explicit-solvent model. If neglected, overestimation of electrostatic coupling between ionizable sites may occur, as will be shown in Sec.…”
Section: B Titratable Co-ions For Charge Levelingmentioning
confidence: 99%
See 2 more Smart Citations
“…We also demonstrated that the potential artifacts are negligible in the hybrid-solvent scheme where GB model is applied to propagating the titration coordinates. 15 However, a varying net charge is a major issue that needs to be addressed for developing an accurate CpHMD method based on the explicit-solvent model. If neglected, overestimation of electrostatic coupling between ionizable sites may occur, as will be shown in Sec.…”
Section: B Titratable Co-ions For Charge Levelingmentioning
confidence: 99%
“…14 Recently, the method was extended to conformational sampling in explicit solvent while propagating the titration coordinates via GB calculations, in an attempt to circumvent the conformational bias of implicit-solvent models while retaining the ability to quickly evaluate solvation free energies. 15 This hybrid-solvent scheme, combined with a pH-based replicaexchange protocol, 15 has been shown to offer more realistic pH-dependent conformational sampling and more accurate pK a prediction for proteins 15 as well as surfactant micelles. 16 Most recently, two groups have reported on the development of CpHMD techniques based solely on explicit-solvent models and testing on small model systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49] Recent studies have shown that CPHMD is a reliable and robust method that is capable of predicting pK a values in a variety of biomolecular systems. [50][51][52][53][54][55][56] Thus, to uncover the pHdependent residues in the CIRV p19 protein involved in siRNA binding stability, we have carried out CPHMD simulations [44][45][46] of the p19 protein dimer in both holo (siRNA-bound) and apo (siRNAfree) forms and determined the pK a values for all titratable residues. These results were then used to calculate the pH-dependent siRNA binding stability profile and corresponding pH-dissociation constant profile.…”
Section: Introductionmentioning
confidence: 99%
“…Processes such as the solvent-mediated proton transfer in close compartments could be fully described. Works carried out by Wallace and Shen (2011) and Swails et al (2014) demonstrated that the RMSD can decrease, respectively, from 0.93 to 0.84 and 1.32 to 0.92 when replacing the implicit solvent by an explicit description. The study was done with hen egg white lysozyme (PDB ids were 2LZT and 3LZT, respectively).…”
Section: Other Common Constant Ph Simulation Methodsmentioning
confidence: 99%